2012
DOI: 10.1177/1010539512448814
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Permanent Tooth Extractions in Taiwan

Abstract: There has been no study in Taiwan on reasons for extraction of permanent teeth. This study aimed to determine the reasons for permanent teeth extraction in Taiwan. This study performed a secondary data analysis based on the National Health Insurance Research Database. The 2009 database was adopted and there are 131 104 records of dental visits in the database; among them, 4958 visits (from 4811 patients) have a coding of extraction. The results showed that dental caries (55.3%) was the main reason for tooth ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
22
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 24 publications
11
22
2
3
Order By: Relevance
“…Regarding the position and type of the extracted teeth, from Graphs 1 and 2, it is clear that the maxillary third molars were the most frequently extracted teeth 13.4%; this is in agreements with previous studies Chrysanthakopoulos NA, Alesia and Khalil, Jafarian and Etebarian, Sahibzada et al 2,4,8,22 Both maxillary and mandibular first molar teeth were commonly extracted in the current study; this is in line with the findings of cited studies Ali et al, Nasreen and Haq, Anyanechi and Chukwuneke, Kashif et al, Al Moaleem et al, 3,7,9,10,16 which could be explained by the early time of eruption of the first molar in the oral cavity. Our findings also agree with the studies of Alesia and Khali, Al Ameer et al, Lee et al, Montandon et al, Chrysanthakopoulos NA,4,5,13,14,21 where anterior teeth were also frequently extracted mainly due to periodontal diseases, which results in the attachment loss with bone resorption around the root and eventually tooth mortality. This agrees with the previous conclusion concerning anterior teeth loss said by Al Ameer et al, Preethanathrs, Al-Shammari et al, Chrysanthakopoulos 5,17,18,21 as shown in Graphs 1 and 2.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the position and type of the extracted teeth, from Graphs 1 and 2, it is clear that the maxillary third molars were the most frequently extracted teeth 13.4%; this is in agreements with previous studies Chrysanthakopoulos NA, Alesia and Khalil, Jafarian and Etebarian, Sahibzada et al 2,4,8,22 Both maxillary and mandibular first molar teeth were commonly extracted in the current study; this is in line with the findings of cited studies Ali et al, Nasreen and Haq, Anyanechi and Chukwuneke, Kashif et al, Al Moaleem et al, 3,7,9,10,16 which could be explained by the early time of eruption of the first molar in the oral cavity. Our findings also agree with the studies of Alesia and Khali, Al Ameer et al, Lee et al, Montandon et al, Chrysanthakopoulos NA,4,5,13,14,21 where anterior teeth were also frequently extracted mainly due to periodontal diseases, which results in the attachment loss with bone resorption around the root and eventually tooth mortality. This agrees with the previous conclusion concerning anterior teeth loss said by Al Ameer et al, Preethanathrs, Al-Shammari et al, Chrysanthakopoulos 5,17,18,21 as shown in Graphs 1 and 2.…”
Section: Discussionsupporting
confidence: 93%
“…The main reason was for prosthetic, followed by orthodontic problems. Unlike our results, Lee et al (11) in their study in Taiwanese (Figure). The bivariate analysis is shown in Table 3.…”
Section: Discussioncontrasting
confidence: 56%
“…Dental caries continues to be the major oral disease responsible for oral discomfort and tooth loss even into old age . While we do not discount the contribution of periodontal diseases, developmental anomalies, oral mucosal and osseous diseases, it remains a fact that caries and its sequelae, pain, tooth loss and edentulism, have been estimated to account for 93–98% of the oral disease burden across the different regions of the world .…”
Section: Trends In Population's Oral Healthmentioning
confidence: 94%